The preliminary study of mirror self-recognition (MSR) on Malayan sun bear (Helarctos malayanus) - Ahmad, Hafandi; Ramali, Mohd Hanafi; H., Azwan; Mohd Noor, Mohd Hezmee; Abu Hassim, Hasliza; Zeid, Zahidah Izzati; Jayaseelan, Kavitha; Tengku Azizan, Tengku Rinalfi Putra (Veterinary Association Malaysia, 2018)
The mirror self-recognition (MSR) is a behavioral technique to determine whether an animal has the ability to identify themselves in front of a mirror. A Malayan sun bear (Helarctos malayanus) was selected from Zoo Negara Malaysia and an acrylic mirror is placed outside of the cage to observe interaction of the animal to the mirror. This study showed that the bear’s behaviour was inconsistent due to the inability of the animal to recognize its own reflection after exposure to the close and open mirror tests. These results suggest that when keeping Malayan sun bears in captivity, putting a mirror as enrichment may promote communication and familiarity between conspecific.